2018
DOI: 10.1242/bio.029223
|View full text |Cite
|
Sign up to set email alerts
|

How does the snakeheadChanna argussurvive in air? The combined roles of the suprabranchial chamber and physiological regulations during aerial respiration

Abstract: This study aimed to test the hypothesis that the aerial survival of the northern snakehead is involved not only with suprabranchial chamber respiration but also with physiological regulations. The aerial survival time and oxygen consumption rate (VO2) were determined in snakeheads with either normal or injured suprabranchial organs. Some hematological and biochemical parameters were assessed during aerial exposure. The results showed that resting VO2 decreased when switching from water to air in both the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Tissue hypoxia results from insu cient oxygen supply, and its serious consequences vary with the degree and environment of hypoxia (Li et al, 2018). Persistent hypoxia is incompatible with normal biological function, so multicellular organisms have evolved solutions to hypoxia at the physical scale and cellular level, include both direct processes (such as oxidative phosphorylation down-regulation and inhibition of fatty acid desaturation) and indirect processes, such as altered expression of hypoxiasensitive transcription factors (Cai et al, 2014;Duan et al, 2018;Liu et al, 2014). This study found that the expression of OrGLUT-1 was signi cantly up-regulated in the CNS and hepatopancreas of O.reevesii.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue hypoxia results from insu cient oxygen supply, and its serious consequences vary with the degree and environment of hypoxia (Li et al, 2018). Persistent hypoxia is incompatible with normal biological function, so multicellular organisms have evolved solutions to hypoxia at the physical scale and cellular level, include both direct processes (such as oxidative phosphorylation down-regulation and inhibition of fatty acid desaturation) and indirect processes, such as altered expression of hypoxiasensitive transcription factors (Cai et al, 2014;Duan et al, 2018;Liu et al, 2014). This study found that the expression of OrGLUT-1 was signi cantly up-regulated in the CNS and hepatopancreas of O.reevesii.…”
Section: Discussionmentioning
confidence: 99%
“…They have flattened heads and possess large scales on their heads, and their eyes are located in the dorsoventral position on the anterior part of the head. They are highly adaptable and can breathe with the help of the suprabranchial organ in the event of a lack of oxygen or being out of water [3]. At present, according to the information published in the Integrated Taxonomic Information System (https://itis.gov/), Channidae is divided Diversity 2024, 16, 346 2 of 14 into the genera Channa and Parachanna.…”
Section: Introductionmentioning
confidence: 99%
“…Although these predictions are explicit, several synbranchiform traits suggest they may have elevated dispersal ability relative to other freshwater fishes, complicating the interpretation of these scenarios. These traits include their ability to tolerate hypoxic aquatic environments using a variety of adaptations for breathing air from the water's surface via air‐breathing organs (Tate et al., 2017), and the ability of some species to traverse over land (Das, 1928; Duan et al., 2018; Hughes & Munshi, 1979; Ishimatsu & Itazawa, 1981).…”
Section: Introductionmentioning
confidence: 99%